Arthur - Greenhut, Robert 1942-; Gordon, Steve 1938-1982; Moore, Dudley 1935-2002; Minnelli, liza 1946-; Gielgud, John 1904-2000 (Burbank, California Warner Home Video, 1997)
Arthur Bach is vary rich- and very drunk most of the time, with a bar bill that reads like the national debt. He also stands to lose his 750-million dollar inheritance if he doesn't marry the most boring blonde on Long Island within a month. Unfortunately, Arthur's just discovered the girl of his dreams. And in his case, love's not only blind but blind drunk.
Music by Burt Bacharach ; Executive producer, Charles H. Joffe.
Dudley Moore, Liza Minnelli, John Gielgud.
VHS format.
In English.
Keywords: Love in motion pictures; Feature films; Comedy films